Knock‐In of the Recurrent R368X Mutation of PRKAR1A that Represses cAMP‐Dependent Protein Kinase A Activation: A Model of Type 1 Acrodysostosis. (24th October 2016) - Le Stunff, Catherine; Tilotta, Francoise; Sadoine, Jérémy; Le Denmat, Dominique; Briet, Claire; Motte, Emmanuelle; Clauser, Eric; Bougnères, Pierre; Chaussain, Catherine; Silve, Caroline
ABSTRACT: In humans, activating mutations in the PRKAR1A gene cause acrodysostosis 1 (ACRDYS1). These mutations result in a reduction in PKA activation caused by an impaired ability of cAMP to dissociate mutant PRKAR1A from catalytic PKA subunits. Two striking features of this rare developmental disease are renal resistance to PTH and chondrodysplasia resulting from the constitutive inhibition of PTHR1/Gsa/AC/cAMP/PKA signaling. We developed a knock‐in of the recurrent ACRDYS1 R368X PRKAR1A mutation in the mouse. No litters were obtained from [R368X]/[+] females (thus no homozygous [R368X]/[R368X] mice). In [R368X]/[+] mice, Western blot analysis confirmed mutant allele heterozygous expression. Growth retardation, peripheral acrodysostosis (including brachydactyly affecting all digits), and facial dysostosis were shown in [R368X]/[+] mice by weight curves and skeletal measurements (μCT scan) as a function of time. [R368X]/[+] male and female mice were similarly affected. Unexpected, however, whole‐mount skeletal preparations revealed a striking delay in mineralization in newborn mutant mice, accompanied by a decrease in the height of terminal hypertrophic chondrocyte layer, an increase in the height of columnar proliferative prehypertrophic chondrocyte layer, and changes in the number and spatial arrangement of proliferating cell nuclear antigen (PCNA)‐positive chondrocytes. Plasma PTH and basal urinary cAMP were significantly higher in [R368X]/[+] compared to WT mice. PTH injection increased urinary cAMP similarly in [R368X]/[+] and WT mice. PRKACA expression was regulated in a tissue (kidney not bone and liver) manner. This model, the first describing the germline expression of a PRKAR1A mutation causing dominant repression of cAMP‐dependent PKA, reproduced the main features of ACRDYS1 in humans. It should help decipher the specificity of the cAMP/PKA signaling pathway, crucial for numerous stimuli. In addition, our results indicate that PRKAR1A, by tempering intracellular cAMP levels, is a molecular switch at the crossroads of signaling pathways regulating chondrocyte proliferation and differentiation. © 2016 American Society for Bone and Mineral Research.